Epidural Steroid Injections in Low Backache: An Overview - Siddharth Jain; Pankaj Kumar Mishra (Research Highlights in Disease and Health Research Vol. 4, 2023)
The purpose of the chapter is to find out the effectiveness of epidural steroid injections in low backache. Epidural steroid injections provide reliable pain relief in patients with low back pain and radicular symptoms but not axial back pain, as depicted by various studies in the literature. The epidural area is injected with steroids to reduce inflammation, relieve pain, and avoid using drugs or surgery. The injections are used to relieve back pain brought on by inflamed and irritated spinal nerve roots. The study concluded that epidural steroid injections can be safely administered three to four times per year, with at least two weeks between injections. Two to three injections are frequently required to effectively relieve pain. If the injections do not provide significant relief, a consultation with the treating doctor is recommended to discuss additional treatment options.